New and noteworthy Volvariella spp. (Volvariellaceae) from Pakistan - Jabeen, Sana; Ijaz, Hira; Ullah, Sadiq; Shahid, Aleena; Sharif, Muhammad Bilal; Aslam, Aqsa; Saeed, Anum; Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2025)
Several species of Volvariella were collected from the Khyber Pakhtunkhwa and Punjab provinces of Pakistan. These species are described based on their morphological features and molecular phylogenetic analysis using sequences from the nrDNA-ITS region. Volvariella alba is described as a new taxon and differs morphologically from V. nivea in having a smooth short stipe with a membranous bi-lobed volva with brown patches. Volvariella roseostriata is another new taxon which differs from morphologically similar species by its brownish pink, radially arranged tuberculate striations on a pinkish white pileus and a saccate, irregularly lobed volva. Both species are distinct from already known based on molecular data. Volvariella biolobata is included as a new record from Pakistan, and V. bombycina has been described for the first time for the country based on molecular phylogenetic analysis. We provide a key to the known species of Volvariella from Pakistan.